2014
DOI: 10.1093/applin/amu060
|View full text |Cite
|
Sign up to set email alerts
|

From One to Multiple Accents on a Test of L2 Listening Comprehension

Abstract: Concerns about the need for assessing multidialectal listening skills for global contexts are becoming increasingly prevalent. However, the inclusion of multiple accents on listening assessments may threaten test fairness because it is not practical to include every accent that may be encountered in the language use domain on these tests. Given this dilemma, this study aimed to determine the extent to which accent strength and familiarity affect comprehension and to provide a defensible direction for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 26 publications
6
52
1
Order By: Relevance
“…44–45) echoed this by saying that “accent can only be understood and defined if there is something to compare it with.” Harding () included more concrete phonological components when he indicated that accents comprised differences in the segmental and suprasegmental features of pronunciation, including variation in vowels and consonant sounds as well as stress and intonation. For the purposes of this study, we support Ockey and French's (, p. 695) construct definition of accent : “the degree to which an individual's speech patterns are perceived to be different from the local variety, and how much this difference is perceived to impact comprehension of listeners who are familiar with the local variety.”…”
Section: The Effect Of Accent On Listening Comprehensionsupporting
confidence: 55%
See 2 more Smart Citations
“…44–45) echoed this by saying that “accent can only be understood and defined if there is something to compare it with.” Harding () included more concrete phonological components when he indicated that accents comprised differences in the segmental and suprasegmental features of pronunciation, including variation in vowels and consonant sounds as well as stress and intonation. For the purposes of this study, we support Ockey and French's (, p. 695) construct definition of accent : “the degree to which an individual's speech patterns are perceived to be different from the local variety, and how much this difference is perceived to impact comprehension of listeners who are familiar with the local variety.”…”
Section: The Effect Of Accent On Listening Comprehensionsupporting
confidence: 55%
“…In the listening assessment literature, the role of the test speaker's L1 accent has been seen as a multifaceted area of inquiry for more than a decade (Llurda, ). On one hand, there has been a push for the inclusion of L1 accent varieties in the listening sections of high‐stakes English exams (Abeywickrama, ; Harding, ; Ockey & French, ; Ockey, Papageorgiou, & French, ). With approximately 505 million nonnative English speakers (OMICS International, ), many native English speakers (NESs) as well as nonnative English speakers (NNESs) are exposed to a wide range of accents in their everyday interactions.…”
Section: Varieties Of English In Assessment Of Listening Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition emerged partly as a result of research which has shown that high-stakes assessments that are rated by local raters who are familiar with the speakers' first language can assign much more lenient ratings than raters who are not familiar with the local first language (Carey, Mannel and Dunn 2011). While some argue for more acceptance of various accents when assessing oral communication (Abeywickrama 2013;Smith and Bisazza 1982), others note the importance of accent in oral communication, and argue that to be fair to test takers, oral communication assessments should carefully consider the accent of the input (Elder and Harding 2008;Ockey and French 2014) and judge the strength of the test takers' accent as a part of their oral communication ability.…”
Section: The Construct Of Oral Communicationmentioning
confidence: 99%
“…Their finding raises the prospect of rater bias if an assessor shares (or is highly familiar with) a speaker's accent -a variable which might need to be controlled for or screened in rater selection for high-stakes tests and research studies alike (Winke, Gass & Myford 2013). 6 It also problematizes the use of speakers with different accents in L2 listening tests intended for test-takers from mixed L1 backgrounds, since listeners' familiarity with the accent used in the prompt could lead to greater item difficulty (Ockey & French 2016).…”
Section: Ucles (1913) Certificate Of Proficiency In English (Cpe) Cmentioning
confidence: 99%